Demystifying Children's Perception of Oral Hygiene and Prevention of Periodontal Diseases: an Experience Report - Santos Sá, Joyce Raianne; Araújo, Ozanna Soares Medeiros de; Oliveira, David Frutuoso de; Alves, Vitória Gabrielle Gouveia; Barbosa, André Luis Fragoso; Rodrigues, Rachel de Queiroz Ferreira; Sousa, João Nilton Lopes de (ARCHIVES OF HEALTH INVESTIGATION, 2023)
Recently, periodontics has been in the limelight when it comes to dentistry. Nonetheless, the population still shows a lack of basic knowledge regarding periodontal health. This shows the need to encourage oral hygiene education, in order to revert this paradigm. The goal of this study was to report the experience of activities to promote periodontal health in children, as well as the materials used, and the results obtained. The activity analyzed was carried out by dentistry students from the Universidade Federal de Campina Grande, participants of the Extension Project on Clinical and Surgical Periodontics (PROEPECC). Activities emphasized orientations regarding periodontal health based on the specific knowledge students needed the most, which was ascertained using a questionnaire that was applied in the first extension activity. It also addressed issues such as healthy eating, hygiene methods, and others. Two classrooms from the elementary school Nelita Nóbrega Queiroz (Patos - PB) were chosen, including a total of 60 children from 5 to 7 years old. Based on the early survey, it was necessary to teach periodontics basics, as only one child had any knowledge on the subject. At the end of the activity, the questionnaire was applied again, revealing that 100% of the sample had been well instructed regarding prevention, concepts, and characteristics of periodontal diseases and oral hygiene. The interaction of the students with the children out of the institutional boundaries enabled innovative experiences and collective practices. For the children involved, it measured their ability to improve their knowledge, especially when it comes to promoting periodontal health, goals reached in the current project.